Caries Preventive Effects of Theobromine Containing Toothpaste on Early Childhood Caries: Preliminary Results - KARGÜL, BETÜL; YILMAZ, MÜESSER AHU (UNIV ZAGREB, SCH DENTAL MEDICINE, 2021)
Objective: Enamel remineralizing effects of theobromine have received much attention from the clinicians. The aim of this study was to investigate the caries preventive effect of theobromine containing toothpaste on children with early childhood caries (ECC). Materials & Methods: Salivary pH, buffering capacity and frequency of Streptococcus mutans (SM) levels were measured. Each child was assigned either fluoridated or theobromine containing toothpaste. The changes were analyzed using Laser Fluorescence system. Statistical analyses were performed. Results: We included 13 children (mean age 4.25) with 145 teeth in the fluoridated toothpaste (Colgate Kids toothpaste) group; 13 children (mean age 4.46) with 115 teeth in theobromine containing toothpaste (Theodent (TM) Kids toothpaste) group. Both toothpastes demonstrated enamel remineralization and were effective in increasing the buffering capacity and pH (p < 0.05). A statistically significant decrease in S. mutans levels was found in both toothpaste groups (p<0.05). Conclusion: Both toothpaste group showed a statistically significant amount of enamel remineralization. Since theobromine had the added benefits of increasing the salivary pH and decreasing the S.mutans levels, theobromine containing toothpastes can be considered effective agents in remineralizing white spot lesions and can be used in prevention of early enamel lesions.
Keywords: Toothpastes; Theobromine; Tooth Remineralization; Preventive Dentistry; Preschool Child; HAMSTER CARIES; ENAMEL SURFACE; 1ST MOLARS; REMINERALIZATION; INHIBITION; EXPERIENCE; FLUORIDE; CHILDREN; LESIONS; COCOA